Investigating the perceptions of college students towards online learning in Oman during the COVID-19 pandemic - AlJabri, Fatma (2020)
The recent outbreak of the COVID-19 pandemic resulted in stopping all face-to-face teaching in higher education institutions (HEIs) all over the world. As a result, online learning was the medium these institutions used to keep the teaching and learning process going on. The Sultanate of Oman was one of the countries that was affected by this pandemic and all its HEIs replaced regular teaching and learning with online learning. This was the first-time bachelor’s degree students take their courses fully online. No recorded previous study explored such situation in the Sultanate of Oman. The perceptions of learners who went through this experience provide valuable information about the effectiveness of the system that was followed by the institutions during that time. This study intends to investigate the perceptions of college students during the COVID-19 pandemic in Oman. An online survey was conducted among the students of one private college in the Sultanate of Oman. The data was analyzed, and the results were discussed. Findings give strong indicators that online learning in HEIs in the Sultanate of Oman during the covid-19 pandemic has had some advantages and some disadvantages that need to be addressed and analyzed. More effort is required from everyone to make online learning better and more productive in Oman.